THE EFFECT OF PRICE AND PRODUCT QUALITY ON CUSTOMER BUYING INTEREST IN TEA FLORA PRODUCTS IN THE BULAK BANTENG AREA, NORTH SURABAYA - Ani Rachmawati; Is Fadhilah (Pedagogic Research-Applied Literacy Journal, 2025)
The increasing trend of iced tea consumption has intensified competition in the beverage sector, making price and product quality the main factors influencing consumer purchasing decisions. This study aims to analyze the effect of price and product quality on customer purchase intention toward Teh Flora in the Bulak Banteng area, North Surabaya. A quantitative approach was used, employing a survey method with a 4-point Likert scale questionnaire. The study involved a sample of 120 respondents from the Bulak Banteng area. Normality testing was conducted using the Kolmogorov-Smirnov test through IBM SPSS Statistics 25 with a significance level of 0.05. The results indicate that price and product quality have a positive and significant influence on purchase intention.